Application of Bioactive Hydrogels for Functional Treatment of Intrauterine Adhesion - Wang, Jingying; Yang, Chao; Xie, Yuxin; Chen, Xiaoxu; Jiang, Ting; Tian, Jing; Hu, Sihui; Lu, Yingli (Frontiers in Bioengineering and Biotechnology, 2021)
Intrauterine adhesion (IUA) is a common endometrial disease and one of the main causes of infertility in women of childbearing age. Current treatment strategies, such as hysteroscopic adhesion resection, hysteroscopic transcervical resection of adhesion (TCRA), the use of local hormone drugs, and anti-adhesion scaffold implantation, do not provide a satisfactory pregnancy outcome for moderate-severe IUA, which presents a great challenge in reproductive medicine. With the development of material engineering, various bioactive and functional hydrogels have been developed using natural and synthetic biomaterials. These hydrogels are not only used as barely physical barriers but are also designed as vectors of hormone drugs, growth factors, and stem cells. These characteristics give bioactive hydrogels potentially important roles in the prevention and treatment of IUA. However, there is still no systematic review or consensus on the current advances and future research direction in this field. Herein, we review recent advances in bioactive hydrogels as physical anti-adhesion barriers, in situ drug delivery systems, and 3D cell delivery and culture systems for seeded cells in IUA treatment. In addition, current limitations and future perspectives are presented for further research guidance, which may provide a comprehensive understanding of the application of bioactive hydrogels in intrauterine adhesion treatment.